A exploração mineira como fator de modernização do território: o potencial do Triângulo Mineiro - Alto Paranaíba - Moreira, Diego Henrique (2016)
This paper analyzes how the mineral activity follows the processes allocated in each social formation and in every historical time in a different way. It is understood that mineral activity corresponds to the demands placed on each historical time and for each social formation differently. Being a break with the modern shapes and if being pretéritas in science to create General and universal, it is during this period that occurs a time revolution in which standards, laws and guidelines of conduct are placed in General for the whole society. It is in this complex process of forming an entire mode of production that the mineral activity, always present in human activities, in the Modern Age, acquires the meaning of goods. So in this way, the interest in mining in the region of the Triângulo Mineiro-Alto Paranaíba stems from the need for understanding of territorial formation in this region as well as its role in Brazil's insertion in the world economy. In order to achieve the goal of presenting a potential diagnosis of mineral exploration in the region of the Triângulo Mineiro-Alto Paranaíba search-perform the cut search space, the natural characteristics that allow the appearance of different minerals, as well as the process of original occupation of the area, mining legislation and its interrelationship inseparable with the process of mineral exploration in general terms , and finally is made the analysis of the data collected showing the mineral potential of the region, giving focus to the main strategic minerals, namely, the phosphate, niobium and diamond. In this way the region of Triângulo Mineiro-Alto Paranaíba, compliant, therefore, cooperation/mediation role between the posts and the different spatial productive circuit causing several processes to coexist in time and space.